PENGARUH PENGGUNAAN LKS KONSTRUKTIVIS DALAM PEMBELAJARAN KREATIF PRODUKTIF TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X DI SMAN 15 PADANG - Afni Aisna Safitri (PILLAR OF PHYSICS EDUCATION, 2014)
The low of student’s achievement for physics learning in SMAN 15 Padang is caused by the lack of student activity in learning process. Constructivism is an approach which points the importance of building knowledge for student by participating actively in learning process. The using of teaching material such as student's worksheet in learning process can be support the learning activity. Student’s worksheet can direct the mindset and create student's independence in learning and finding knowledge. Therefore, a research has been implemented which aim is to know the influence of student’s construtivisme worksheet in creative productive learning towards to students physics learning outcome grade X SMAN 15 Padang. The population of quasi experiment research which design randomized control group only design are all of class X SMA Negeri 15 Padang that is registered in academic years 2013/2014. The technique of selecting sample is Cluster Random Sampling. Research shown that there is an influence of student’s construtivisme worksheet in creative productive learning towards to students physics learning outcome grade X SMAN 15 Padang quantitatively on significant level 0.05. So that the using of student’s construtivisme worksheet in creative productive learning can increase student’s learning outcome in kognitive, affective, and psychomotor aspecits